THE INFLUENCE OF LEADERSHIP STYLE, WORK ENVIRONMENT AND WORK DISCIPLINE ON THE PERFORMANCE OF VILLAGE OFFICIALS IN THE DISTRICT GANTARANG KEKE BANTAENG REGENCY - Husnul Ilma Amalia; I Nengah Suarmanayasa; Ni Made Suci (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to empirically demonstrate the influence of leadership style, work environment, and work discipline on the performance of village officials in Gantarang Keke District, Bantaeng Regency. The population in this study was all 52 village officials in Gantarang Keke District, Bantaeng Regency. Sampling using saturated sampling techniques so that the entire population is used as a sample study. Collection data use questionnaire with scale Likert scale 1–5. The data analysis technique used multiple linear regression analysis with the help of the IBM SPSS application. The results of the study showed that partially the leadership style and discipline work has a positive influence and significantly on the performance of village officials, while the work environment has a negative and significant effect on the performance of village officials. Simultaneously, these three independent variables have a significant effect on the performance of village officials in Gantarang Keke District, Bantaeng Regency.